Assessment of the Economic Impact Associated with the Recreational Scallop Season in Hernando County, Florida - Brittany Hall-Scharf; Charles M. Adams; Alan W. Hodges; Stephen Geiger (EDIS, 2018)
Recreational scalloping has become an increasingly popular activity within the Big Bend region of Florida and Hernando County is the southern extent of healthy, harvestable bay scallop populations.  A previous study (Stevens, et al, 2003) found that the recreational scallop fishery generated 35 jobs and $1.6 million in economic impact to the economy of neighboring Citrus County in 2003. State resource managers and County administrators expressed a need to know how the recreational scallop season impacts the local economies.